Evaluating the impact of COVID-19 on mental health of the public in Jordan: A cross-sectional study - Yara A. Suleiman; Derar H. Abdel-Qader; Bashar A. Suleiman; Adel H. Suleiman; Salim Hamadi; Ahmad Z. Al Meslamani (GarVal Editorial Ltda., 2022)
Context: Although the COVID-19 pandemic was expected to have a significant impact on the mental health of the Jordanian population, there have been few studies to investigate the nature and magnitude of the impact. Aims: To assess the potential psychiatric disorders induced by the current pandemic and evaluate the relevant risk factors. Methods: A cross-sectional national survey-based study was conducted over 3 months (August to October, 2020) in 12 governorates in Jordan using random proportionate sampling; the questionnaire being answered in face-to-face interviews with a randomly selected sample of the adult population aged 18 years and older, to collect data from 1820 individuals. The modified Kessler scale was validated by a multidisciplinary committee. SPSS V26 was used for data analysis. Results: Findings indicated that due to the COVID-19 pandemic, 11.4% (207/1820) of participants had severe mental disorders, 25.4% (462/1820) moderate mental disorders, while 34.7% (632/1820) were without any mental issues. Predictors for severe mental disorder were: monthly income (<500 JOD) {OR: 3.6, 95%CI: 3.12-7.68, p = 0.01}, Employment status (unemployed) {OR: 2.4, 95%CI: 1.45-4.96, p = 0.001}, and those diagnosed with diabetes {OR: 1.9, 95%CI: 1.13-3.63, p = 0.03}. Conclusions: COVID-19 pandemic had a notable impact on the mental health of people living in Jordan. People who had low monthly income (<500 JOD) or were unemployed were mostly affected as well as diabetes patients. These cases were recognized as significant risk factors for moderate and severe mental disorders. Appropriate psychiatric and economic interventions were recommended to improve the mental preparedness for pandemics among the population in Jordan.